Video analysis of the locomotory behaviour of Aedes aegypti and Ae. japonicus mosquitoes under different temperature regimes in a laboratory setting. (April 2022) - Ziegler, Raphaela; Blanckenhorn, Wolf U.; Mathis, Alexander; Verhulst, Niels O.
Abstract: Mosquito-borne diseases impose a high burden on human and animal health. Temperature strongly influences the physiology and life cycle of mosquitoes, but also the development and/or propagation of the pathogens they transmit. Thus, the vector capacity of mosquitoes depends strongly on temperature and their behavioural thermoregulation through microhabitat selection. Expanding on a previous study of static thermal preferences, the locomotory dynamics of temperate Aedes japonicus (reared from eggs collected in the field) and tropical Ae. aegypti (from a laboratory colony) was investigated at constant temperatures (10 °C, 25 °C, 40 °C) and in temperature gradients (10–20 °C, 20–30 °C, 30–40 °C). Blood-fed or non-blood-fed female mosquitoes were released in groups of 15 individuals into a Plexiglas box positioned on two thermoregulators connected by an aluminium plate to automatically monitor by video analysis mosquito flying, walking and resting duration, covered distances and velocity. Mosquitoes were predominantly resting, followed by walking and flying. At constant 10 °C, flights were rare and brief, and walking was slow. Most activity was observed at 25 °C for Ae. japonicus and 40 °C for Ae. aegypti . In the 30–40 °C gradient, activity of Ae. aegypti increased towards the cold end, suggesting active avoidance of very high temperatures. In the 20–30 °C gradient, edge effects were prominent, nevertheless revealing a greater proportion of mosquitoes gathered at the cooler end. Video analysis showed that this effect was not caused by a cold trap but represents true thermal preference. In the coolest gradient (10–20 °C), mosquitoes were active in all sectors without displaying a preference for either side. Overall, both the tropical and temperate mosquito species preferred cooler temperatures and actively avoided the hottest temperatures. Further studies with infected mosquitoes should provide important insights for developing models of vector-borne disease outbreaks. Graphical abstract: Image 1 Highlights: Mosquitoes were least active and hardly flying at 10 °C. Above 10 °C there is no cold trap and mosquitoes prefer cooler temperatures. Both mosquito species avoided 40 °C on a temperature gradient. Blood-fed mosquitoes were less active than non-blood-fed ones. Understanding thermal preference is crucial for predicting mosquito vector capacity.